THE IMPACT OF EATING HABITS ON DENTAL HEALTH (International journal of artificial intelligence, 2025)
This article provides a comprehensive and in-depth analysis of the impact of dietary habits on dental health. It examines how the quality and quantity of daily food intake, including the composition of consumed foods and their usage patterns, affect tooth enamel and the oral microbiome. The article highlights the role of sugars, acids, and other food components—particularly sugary and acidic products—in the development of dental caries, enamel damage, and the proliferation of harmful oral bacteria. Furthermore, the importance of a diet rich in vitamins and minerals—especially calcium, phosphorus, and vitamins A, C, and D—in strengthening teeth and maintaining oral health is discussed. Healthy nutrition not only strengthens tooth enamel but also ensures the health of the oral mucosa and enhances immunity. The article also explores the connection between diet and oral hygiene, emphasizing that proper and balanced eating habits combined with regular and correct dental care help prevent dental diseases such as caries and inflammation. Excessive consumption of sugary products and poor dietary habits negatively affect dental health and increase the risk of oral diseases. This article is based on modern scientific research, dental practice results, and nutritional recommendations, emphasizing the importance of proper dietary culture in maintaining dental health. It aims to provide readers with practical guidelines on improving oral hygiene, paying attention to dietary habits, and preventing oral diseases. Additionally, it stresses the importance of a comprehensive approach to shaping a healthy lifestyle and strengthening oral and dental health.